Penegakan Hukum terhadap Pelaku Penyalahgunaan Penyebaran Data Pribadi Melalui Barcode Ditinjau dari UU ITE dan UU Nomor 27 Tahun 2022 Tentang (UU PDP) - Kadek Reza Ayuning Pranindya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Personal data dissemination is a new type of crime that has emerged in the digital world. The rapid development of technology has led to various innovations in data storage, one of which is through barcode technology. Although it provides convenience, this technology also opens up new gaps in cybercrime, especially the misuse and dissemination of personal data stored in barcodes. The impacts of the spread of personal data include damage to personal reputation due to the widespread dissemination of personal data on the internet, the emergence of cyber bullying and sexual harassment, personal data that has the potential to be sold, and the distress and psychological trauma experienced by victims of personal data dissemination. The purpose of this study is to analyze how law enforcement against perpetrators of abuse of the spread of personal data stored in barcodes is reviewed from the ITE Law and the PDP Law, and identify preventive efforts that can be made to prevent these crimes. This research uses a normative juridical approach method used to examine applicable legal norms related to personal data protection. With a statute approach, books, scientific journals, and the internet. The results showed that, although the ITE Law does not specifically regulate barcode technology, the protection of personal data stored in barcodes is still subject to the provisions of the ITE Law and Law Number 27 of 2022 concerning Personal Data Protection.